Tuberculosis-loop-mediated isothermal amplification implementation in Cameroon: Challenges, lessons learned and recommendations - Valerie F. Donkeng-Donfack; Suzanne M. Ongoulal; Yvonne J. Djieugoue; Yannick K. Simo; Henri Manga; Danielle A.D. Tollo; Edwige M.A. Belinga; Vincent Mbassa; Jean L. Abena; Sara Eyangoh (AOSIS, 2022)
Background: Until 2016, microscopy was the main tool for the early detection of pulmonary tuberculosis in Cameroon, especially in remote settings. Due to the poor sensitivity of microscopy, there was a need to implement a molecular assay in order to improve tuberculosis case detection. Intervention: In 2017, tuberculosis loop-mediated isothermal amplification (TB-LAMP), a molecular rapid diagnostic test recommended by the World Health Organization, was implemented in Cameroon as a replacement test of microscopy for initial diagnosis of pulmonary tuberculosis and also as a follow-on test to microscopy for smear-negative sputum specimens. A roll out plan for TB-LAMP implementation in Cameroon had been developed from January 2017 to April 2017, followed by initial implementation at four sites in May 2017. Additional sites were added progressively. Lessons learnt: The use of TB-LAMP as a follow-on test to microscopy for smear-negative sputum specimens helped in the detection of tuberculosis in 14.77% of those who were sputum-smear negative in 2019. Tuberculosis-loop-mediated isothermal amplification usage as an initial test, followed by testing with Xpert MTB/RIF for rapid tuberculosis and rifampicin resistance detection during tuberculosis mass screening campaigns, reduced the turn-around time by 73.23% as compared to when the Gene Xpert instrument was used alone. Recommendations: The implementation and scaling up of TB-LAMP in Cameroon contributed to increase access to tuberculosis molecular diagnosis in remote settings and as such improved tuberculosis case notification. However, to better enhance this notification and optimise the use of a TB-LAMP instrument, a suitable sample transport system is recommended.